plant economics spectrum in Mediterranean forests along environmental gradients: is there coordination among leaf, stem and root traits? - Riva, Enrique G; Tosto, Ambra; Pérez‐Ramos, Ignacio M; Navarro‐Fernández, Carmen M; Olmo, Manuel; Anten, Niels P.R; Marañón, Teodoro; Villar, Rafael; Bello, Francesco (Journal of vegetation science, 2016)
QUESTIONS: Is there any evidence of coordination among leaf, stem and root traits, and thereby of the existence of a plant economics spectrum at the species and community level in Mediterranean forests? Are these traits related to plant size and seed mass? LOCATION: Mediterranean forests and shrublands, Sierra Morena mountains, Córdoba, southern Spain. METHODS: We selected nine woody plant communities along a natural local gradient of soil water and nutrient availability. We measured key leaf, stem, root and whole‐plant traits for 38 dominant woody plant species. The variation across species of 15 functional traits (of the leaf, stem and root) was analysed and coordination among them was tested. We explored the relationships between these traits (hereafter ‘resource‐use traits’ due to their close association with the acquisition–conservation trade‐off) and plant height and seed mass. Finally, we compared results at species level with those calculated at community level, considering community‐weighted means (CWMs). RESULTS: We found a significant coordination between traits belonging to different plant organs, and propose the existence of a plant economics spectrum in Mediterranean forests along the environmental gradient. However, weaker relationships were found within groups of species under similar environmental conditions. We did not find the expected orthogonal relationships between plant height, seed mass and resource‐use traits. Relationships among functional traits were stronger at the community level than at the species level. CONCLUSIONS: This study reveals a high degree of functional coordination between traits belonging to different plant organs at both species and community level, and suggests the existence of a plant economics spectrum across 38 Mediterranean woody plant species. However, this general trend of functional coordination between organs became weaker or disappeared when considering restricted groups of species belonging to environmentally similar sites (e.g. dry vs wet sites), suggesting that the diversification of strategies within communities is not related to the economics spectrum at a lower spatial scale. Interestingly, the high degree of coordination between resource‐use traits and seed mass at the community level seems to support the tolerance–fecundity model, which predicts an inverse relationship between fecundity and stress tolerance.